Analisis Potensi dan Strategi Pengembangan Wisata Kali Jompo Kecamatan Sukorambi Kabupaten Jember - Setyawan, Dimas Rizky; Sobah, Naqiyyah Nada; Ahmadyani, Zamroji; Fida, Hana Rahma; Paramita, Avidya Rahma; Prabowo, Rachmat Udhi (Universitas Galuh, 2024)
Jember Regency is an area that has many tourism sectors and opportunities for regional progress. One of them is the Kali Jompo Tourism which has tourist attractions in the form of river flows and natural beauty. The purpose of writing this research is to determine the potential and strategy for developing Kali Jompo agrotourism at the village, sub-district and district scale. The method used in this research is a qualitative descriptive method and uses a qualitative approach using the IFE, EFE and SWOT matrices. The results of the analysis show that there are 9 internal factors and 7 external factors and obtain 8 alternative strategies for developing Kali Jompo agrotourism. The strategic priorities obtained are exploiting tourist interest by increasing nature-based uniqueness, increasing the contribution of local communities in developing agrotourism, and improving the quality of human resources and organizational management.